Spatial Configuration and Social Integration in the Residential Area of Benteng Keraton Buton - Pratama, Yusuf Vladimir; Asikin, Damayanti; Antariksa (RUAS, 2025)
The complexity of settlements is shaped by the diversity of user activities and the intensity of social interactions, both of which are influenced by accessibility and spatial configuration. Connectivity systems play a crucial role in linking shared spaces and public services, thereby supporting social and economic activities. This study aims to evaluate the efficiency of spatial configuration patterns in Benteng Keraton Buton using the space syntax method, combined with Geographic Information System (GIS) overlays. Space syntax analysis is employed to assess accessibility based on three key variables: connectivity, integration, and spatial intelligibility. The findings reveal that public spaces and key facilities are concentrated in areas with high levels of accessibility, while areas with low connectivity tend to experience spatial isolation. These results support existing theories of spatial configuration, which propose that accessibility influences the intensity of space utilization and patterns of social interaction. This study offers new insights into the spatial organization of historical settlements and presents a data-driven approach to inform preservation strategies and the sustainable management of similar heritage areas.